2005
DOI: 10.1021/bi0505767
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Azide Occupies the Chloride Binding Site near the Manganese Cluster in Photosystem II

Abstract: The effect of adding azide to photosystem II (PS II) membrane samples (BBY preparation), with or without chloride, has been investigated using continuous wave (CW) and pulsed EPR spectroscopy. In the BBY samples with 25 mM chloride, we observed that the inhibition induced by azide is partly recovered by the addition of bicarbonate. Electron spin-echo envelope modulation (ESEEM) was used to search for spin transitions of 15N nuclei magnetically coupled to the S2 state Mn cluster (multiline EPR signal form) in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…However, they did not provide any information about the number and location of Cl Ϫ ions within the OEC. The inhibition of particular S-state transitions upon depletion of Cl Ϫ has been taken as evidence of the close proximity of Cl Ϫ to the Mn 4 Ca cluster, a proximity that also was suggested by studies of electron spin echo envelope modulation (19,20) and Fourier transform infrared spectroscopic studies (21). Recent EXAFS studies, however, suggested that Cl Ϫ ions do not bind to the Mn 4 Ca cluster in its S 1 state, and that no Cl Ϫ is present within a distance of 5 Å from the metal center (13).…”
mentioning
confidence: 87%
“…However, they did not provide any information about the number and location of Cl Ϫ ions within the OEC. The inhibition of particular S-state transitions upon depletion of Cl Ϫ has been taken as evidence of the close proximity of Cl Ϫ to the Mn 4 Ca cluster, a proximity that also was suggested by studies of electron spin echo envelope modulation (19,20) and Fourier transform infrared spectroscopic studies (21). Recent EXAFS studies, however, suggested that Cl Ϫ ions do not bind to the Mn 4 Ca cluster in its S 1 state, and that no Cl Ϫ is present within a distance of 5 Å from the metal center (13).…”
mentioning
confidence: 87%
“…While there is compelling biochemical evidence for a functional role of Cl K (van Gorkom & Yocum 2005), it is controversial whether it is (in some S states) a direct ligand of the Mn 4 O x Ca cluster. Binding of the Cl K analogue azide within 5 Å of the Mn 4 O x Ca cluster was demonstrated by electron spin-echo envelope modulation (ESEEM) spectroscopy (Yu et al 2005). Similarly, extended EXAFS measurements show an extra peak that may be assigned to Cl K (Pushkar et al 2007).…”
Section: Introductionmentioning
confidence: 93%
“…[232][233][234] The results of a recent combined EPR-FTIR study are consistent with N 3 À binding in the immediate vicinity of the Mn cluster and show that Cl À binding is competitive with N 3 À binding at this site. [235] McEvoy and Brudvig [35] suggested that activation by Cl À binding to Mn(4) could occur by coordination expansion or Cl À bridging between Ca and Mn(4). In either case, a coordinated anion could play an indirect role through its electronic influence on pK a values and intermolecular proton transfer.…”
Section: Angewandte Chemiementioning
confidence: 99%